At Westonci.ca, we connect you with the answers you need, thanks to our active and informed community. Discover the answers you need from a community of experts ready to help you with their knowledge and experience in various fields. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
To determine the solutions to the system of equations and sort the given coordinate points based on whether they are solutions or not, we follow these steps:
First, we need to solve the following system of equations:
[tex]\[ \begin{cases} 2x + y = 10 \quad \text{(Equation 1)} \\ 3x - y = 5 \quad \text{(Equation 2)} \end{cases} \][/tex]
1. Solving the system of equations:
Start by solving Equation 1 for [tex]\( y \)[/tex]:
[tex]\[ y = 10 - 2x \][/tex]
Substitute [tex]\( y = 10 - 2x \)[/tex] into Equation 2:
[tex]\[ 3x - (10 - 2x) = 5 \][/tex]
Simplify and solve for [tex]\( x \)[/tex]:
[tex]\[ 3x - 10 + 2x = 5 \\ 5x - 10 = 5 \\ 5x = 15 \\ x = 3 \][/tex]
Substitute [tex]\( x = 3 \)[/tex] back into Equation 1 to find [tex]\( y \)[/tex]:
[tex]\[ 2(3) + y = 10 \\ 6 + y = 10 \\ y = 4 \][/tex]
Therefore, the solution to the system is [tex]\( (x, y) = (3, 4) \)[/tex].
2. Identifying the solution and non-solution points:
Let's check each given point to see if it satisfies both equations.
- [tex]\( (14, 1) \)[/tex]
[tex]\[ 2(14) + 1 = 28 + 1 = 29 \quad \text{(not 10)} \\ 3(14) - 1 = 42 - 1 = 41 \quad \text{(not 5)} \][/tex]
Hence, [tex]\( (14, 1) \)[/tex] is not a solution.
- [tex]\( (3, 7) \)[/tex]
[tex]\[ 2(3) + 7 = 6 + 7 = 13 \quad \text{(not 10)} \\ 3(3) - 7 = 9 - 7 = 2 \quad \text{(not 5)} \][/tex]
Hence, [tex]\( (3, 7) \)[/tex] is not a solution.
- [tex]\( (1, 3) \)[/tex]
[tex]\[ 2(1) + 3 = 2 + 3 = 5 \quad \text{(not 10)} \\ 3(1) - 3 = 3 - 3 = 0 \quad \text{(not 5)} \][/tex]
Hence, [tex]\( (1, 3) \)[/tex] is not a solution.
- [tex]\( (2, 9) \)[/tex]
[tex]\[ 2(2) + 9 = 4 + 9 = 13 \quad \text{(not 10)} \\ 3(2) - 9 = 6 - 9 = -3 \quad \text{(not 5)} \][/tex]
Hence, [tex]\( (2, 9) \)[/tex] is not a solution.
- [tex]\( (5, 4) \)[/tex]
[tex]\[ 2(5) + 4 = 10 + 4 = 14 \quad \text{(not 10)} \\ 3(5) - 4 = 15 - 4 = 11 \quad \text{(not 5)} \][/tex]
Hence, [tex]\( (5, 4) \)[/tex] is not a solution.
- [tex]\( (1, 13) \)[/tex]
[tex]\[ 2(1) + 13 = 2 + 13 = 15 \quad \text{(not 10)} \\ 3(1) - 13 = 3 - 13 = -10 \quad \text{(not 5)} \][/tex]
Hence, [tex]\( (1, 13) \)[/tex] is not a solution.
- [tex]\( (2, 4) \)[/tex]
[tex]\[ 2(2) + 4 = 4 + 4 = 8 \quad \text{(not 10)} \\ 3(2) - 4 = 6 - 4 = 2 \quad \text{(not 5)} \][/tex]
Hence, [tex]\( (2, 4) \)[/tex] is not a solution.
- [tex]\( (7, 7) \)[/tex]
[tex]\[ 2(7) + 7 = 14 + 7 = 21 \quad \text{(not 10)} \\ 3(7) - 7 = 21 - 7 = 14 \quad \text{(not 5)} \][/tex]
Hence, [tex]\( (7, 7) \)[/tex] is not a solution.
3. Summary:
- Solution to the System:
[tex]\[ (3, 4) \][/tex]
- Not a Solution to the System:
[tex]\[ (14, 1), (3, 7), (1, 3), (2, 9), (5, 4), (1, 13), (2, 4), (7, 7) \][/tex]
First, we need to solve the following system of equations:
[tex]\[ \begin{cases} 2x + y = 10 \quad \text{(Equation 1)} \\ 3x - y = 5 \quad \text{(Equation 2)} \end{cases} \][/tex]
1. Solving the system of equations:
Start by solving Equation 1 for [tex]\( y \)[/tex]:
[tex]\[ y = 10 - 2x \][/tex]
Substitute [tex]\( y = 10 - 2x \)[/tex] into Equation 2:
[tex]\[ 3x - (10 - 2x) = 5 \][/tex]
Simplify and solve for [tex]\( x \)[/tex]:
[tex]\[ 3x - 10 + 2x = 5 \\ 5x - 10 = 5 \\ 5x = 15 \\ x = 3 \][/tex]
Substitute [tex]\( x = 3 \)[/tex] back into Equation 1 to find [tex]\( y \)[/tex]:
[tex]\[ 2(3) + y = 10 \\ 6 + y = 10 \\ y = 4 \][/tex]
Therefore, the solution to the system is [tex]\( (x, y) = (3, 4) \)[/tex].
2. Identifying the solution and non-solution points:
Let's check each given point to see if it satisfies both equations.
- [tex]\( (14, 1) \)[/tex]
[tex]\[ 2(14) + 1 = 28 + 1 = 29 \quad \text{(not 10)} \\ 3(14) - 1 = 42 - 1 = 41 \quad \text{(not 5)} \][/tex]
Hence, [tex]\( (14, 1) \)[/tex] is not a solution.
- [tex]\( (3, 7) \)[/tex]
[tex]\[ 2(3) + 7 = 6 + 7 = 13 \quad \text{(not 10)} \\ 3(3) - 7 = 9 - 7 = 2 \quad \text{(not 5)} \][/tex]
Hence, [tex]\( (3, 7) \)[/tex] is not a solution.
- [tex]\( (1, 3) \)[/tex]
[tex]\[ 2(1) + 3 = 2 + 3 = 5 \quad \text{(not 10)} \\ 3(1) - 3 = 3 - 3 = 0 \quad \text{(not 5)} \][/tex]
Hence, [tex]\( (1, 3) \)[/tex] is not a solution.
- [tex]\( (2, 9) \)[/tex]
[tex]\[ 2(2) + 9 = 4 + 9 = 13 \quad \text{(not 10)} \\ 3(2) - 9 = 6 - 9 = -3 \quad \text{(not 5)} \][/tex]
Hence, [tex]\( (2, 9) \)[/tex] is not a solution.
- [tex]\( (5, 4) \)[/tex]
[tex]\[ 2(5) + 4 = 10 + 4 = 14 \quad \text{(not 10)} \\ 3(5) - 4 = 15 - 4 = 11 \quad \text{(not 5)} \][/tex]
Hence, [tex]\( (5, 4) \)[/tex] is not a solution.
- [tex]\( (1, 13) \)[/tex]
[tex]\[ 2(1) + 13 = 2 + 13 = 15 \quad \text{(not 10)} \\ 3(1) - 13 = 3 - 13 = -10 \quad \text{(not 5)} \][/tex]
Hence, [tex]\( (1, 13) \)[/tex] is not a solution.
- [tex]\( (2, 4) \)[/tex]
[tex]\[ 2(2) + 4 = 4 + 4 = 8 \quad \text{(not 10)} \\ 3(2) - 4 = 6 - 4 = 2 \quad \text{(not 5)} \][/tex]
Hence, [tex]\( (2, 4) \)[/tex] is not a solution.
- [tex]\( (7, 7) \)[/tex]
[tex]\[ 2(7) + 7 = 14 + 7 = 21 \quad \text{(not 10)} \\ 3(7) - 7 = 21 - 7 = 14 \quad \text{(not 5)} \][/tex]
Hence, [tex]\( (7, 7) \)[/tex] is not a solution.
3. Summary:
- Solution to the System:
[tex]\[ (3, 4) \][/tex]
- Not a Solution to the System:
[tex]\[ (14, 1), (3, 7), (1, 3), (2, 9), (5, 4), (1, 13), (2, 4), (7, 7) \][/tex]
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.